2003
DOI: 10.1103/physrevlett.90.097201
|View full text |Cite
|
Sign up to set email alerts
|

Control of Interlayer Exchange Coupling inFe/Cr/FeTrilayers by Ion Beam Irradiation

Abstract: The manipulation of the antiferromagnetic interlayer coupling in epitaxial Fe/Cr/Fe(001) trilayers by 5 keV He ion beam irradiation has been investigated. It is shown that even for irradiation with low fluences a drastic change in strength of the coupling appears. For thin Cr spacers (below 0.6-0.7 nm) it decreases with fluence, becoming ferromagnetic for fluences above 2x10(14) ions/cm(2). The effect is connected with the creation of magnetic bridges in the layered system due to atomic exchange events caused … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 30 publications
(25 reference statements)
3
44
0
Order By: Relevance
“…It has been shown that irradiation with keV ions is an efficient method to modify the properties of many magnetic thin film systems, such as CoPt multilayers with perpendicular anisotropy, [12,13,14,15] exchange bias bilayers, [16,17,18] or interlayer exchange coupled trilayers. [19,20,21] Moreover, it was demonstrated that such modifications can be performed with high spatial resolution, making ion irradiation an attractive patterning tool in view of technological applications. [12,13,17,18,21,22] In this work we demonstrate that the magnetic and, in particular, the magneto-optical properties of CFS Heusler alloys can also be modified by means of keV ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that irradiation with keV ions is an efficient method to modify the properties of many magnetic thin film systems, such as CoPt multilayers with perpendicular anisotropy, [12,13,14,15] exchange bias bilayers, [16,17,18] or interlayer exchange coupled trilayers. [19,20,21] Moreover, it was demonstrated that such modifications can be performed with high spatial resolution, making ion irradiation an attractive patterning tool in view of technological applications. [12,13,17,18,21,22] In this work we demonstrate that the magnetic and, in particular, the magneto-optical properties of CFS Heusler alloys can also be modified by means of keV ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that the ion-induced intermixing of atoms at the interfaces can dramatically affect the properties of thin magnetic multilayers 24,25 or capped films, 26 even at doses so low that no etching occurs. In the case of single and noncapped magnetic layers, ion irradiation has two effects.…”
Section: Effect Of Fib Patterningmentioning
confidence: 99%
“…Also the 200 MeV Ag-ion irradiation led to a decrease in GMR effect in Fe/Cr multilayers [7]. Epitaxial Fe/Cr/Fe(0 0 1) trilayers with small thickness of Cr spacer (t Cr ≤ 0.7 nm) irradiated by 5 keV He ions showed a monotonic decrease in antiferromagnetic coupling strength |J AF | with increasing ions dose [4]. However, for t Cr ≥ 0.7 nm, |J AF | initially slightly increases and then decreases.…”
Section: Introductionmentioning
confidence: 94%
“…Presently, antiferromagnetically coupled multilayers are applied not only as magnetoresistance sensors but also as artificial antiferromagnets or antiferromagnetically coupled media. For certain applications, ion irradiation may be effectively used to laterally modify the magnetic properties of such structures after preparation [4]. Therefore, the correlation between the changes of microstructure related to implantation and interlayer coupling and/or GMR effect of multilayers seems to be of interest.…”
Section: Introductionmentioning
confidence: 99%